Macrocyclic prolinyl acyl guanidines as inhibitors of β-secretase (BACE). Issue 22 (15th November 2015) - Boy, Kenneth M.; Guernon, Jason M.; Wu, Yong-Jin; Zhang, Yunhui; Shi, Joe; Zhai, Weixu; Zhu, Shirong; Gerritz, Samuel W.; Toyn, Jeremy H.; Meredith, Jere E.; Barten, Donna M.; Burton, Catherine R.; et al.
Graphical abstract: Abstract: The synthesis, evaluation, and structure–activity relationships of a class of acyl guanidines which inhibit the BACE-1 enzyme are presented. The prolinyl acyl guanidine chemotype (7c ), unlike compounds of the parent isothiazole chemotype (1), yielded compounds with good agreement between their enzymatic and cellular potency as well as a reduced susceptibility to P-gp efflux. Further improvements in potency and P-gp ratio were realized via a macrocyclization strategy. The in vivo profile in wild-type mice and P-gp effects for the macrocyclic analog21c is presented.